2014
DOI: 10.1007/s00436-014-4122-3
|View full text |Cite
|
Sign up to set email alerts
|

First report of Troglostrongylus brevior in a kitten in Greece

Abstract: The first case of a natural infestation with Troglostrongylus brevior in a kitten in Greece is described here. A ∼40-day-old stray cat was referred to a private veterinary clinic with signs of respiratory distress. First stage larvae of a metastrongyloid nematode were observed in the wet mount faecal preparation. Despite an anthelmintic treatment, the respiratory signs worsened and the kitten died 2 days later. The larvae in the faeces were identified morphologically and genetically as T. brevior. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 14 publications
0
42
0
Order By: Relevance
“…in domestic hosts Traversa and Di Cesare 2013;Falsone et al 2014;Traversa 2014). After the first descriptions of T. brevior in F. s. libyca (Gerichter 1949), it was recorded only in a wildcat and a feral domestic cat from Italy (Paggi 1959) and in domestic cats from the European Islands of Ibiza, Sardinia, Sicily, and Crete (Jefferies et al 2010;Brianti et al 2012;Diakou et al 2014;Tamponi et al 2014) and in central and southern Italy Di Cesare et al 2014a;. Some studies (Beraldo et al 2014;Falsone et al 2014;Steeb et al 2014; this study) suggest that the European wildcat is the natural host of T. brevior and that spillover to domestic cats may occur in some enzootic areas.…”
Section: Discussionmentioning
confidence: 99%
“…in domestic hosts Traversa and Di Cesare 2013;Falsone et al 2014;Traversa 2014). After the first descriptions of T. brevior in F. s. libyca (Gerichter 1949), it was recorded only in a wildcat and a feral domestic cat from Italy (Paggi 1959) and in domestic cats from the European Islands of Ibiza, Sardinia, Sicily, and Crete (Jefferies et al 2010;Brianti et al 2012;Diakou et al 2014;Tamponi et al 2014) and in central and southern Italy Di Cesare et al 2014a;. Some studies (Beraldo et al 2014;Falsone et al 2014;Steeb et al 2014; this study) suggest that the European wildcat is the natural host of T. brevior and that spillover to domestic cats may occur in some enzootic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Troglostrongylus sp. was described in the twenties (Vevers, 1923) and then neglected until recently, when the rediscovery of this parasite in single European countries such as Spain (Jefferies et al, 2010), Italy (Brianti et al, 2012;, Greece (Diakou et al, 2014) and Bosnia-Herzegovina (Alic et al, 2015) was reported. The adult nematodes of the latter can be easily differentiated from A. abstrusus: Troglostrongylus sp.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, another respiratory metastrongyloid, Troglostrongylus brevior (Metastrongyloidea, Crenosomatidae), previously described over the last century in wild felids from the Middle East, has been recorded in domestic cats from Mediterranean Europe (1,2). Recently, the almost unknown heartworm Angiostrongylus chabaudi (Metastrongyloidea, Angiostrongylidae), recorded only in the last century in wildcats until recently (3), has been found in two domestic cats from Italy (4,5).…”
mentioning
confidence: 99%